Cirebon Melet: Smart Society - Permata, Mochamad Rizky; Aditya , Reynanda Rizky; Wulandari, Sri; Lestari, Aghnia Dian (PT FORMOSA CENDEKIA GLOBAL, 2024)
The rapid development of technology provides easy access to information. The success of the community in utilizing the internet optimally is the key to realizing a Smart City. Smart City in Cirebon City has one of the programs called